Reasons for chronic existence of prison congestion in Tanzania: critical analysis of the law and practice at Musoma prison - Matagi, Peter Richard (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the award of Degree of Master of Law in Constitutional and Administrative Law of Mzumbe University